Between Divine Destiny and Economic Transactions: A Qualitative Study of Underprivileged People's Perceptions of the Role of Education - Aeni Nur Khofifah; Ubaidillah; Karina Milatu Azka; Siti Nur Khusnul Khotimah (Social Journal of Studies in Education, 2026)
The aim of this study is to critically analyze the dynamics of poor people's perceptions in Sukorejo Village, Kendal, Indonesia regarding whether education functions as a liberating theological intervention or merely as a material necessity for survival. This research employs a qualitative approach with a case study design. Participants were selected purposively, and data were collected through in-depth interviews, participatory observation, and document analysis. Data analysis used the Miles and Huberman interactive model. The findings reveal a dialectical tension between spirituality and economic pragmatism. Community perspectives are divided into three orientations: education as divine destiny, education as an economic transaction, and education as a spiritual-material hybrid. The hybrid perspective is the most dominant but often constrained by economic pressure. This study identifies a hermeneutical meaning crisis as a root problem, where poverty is not only financial but also related to limited understanding of education’s role. This research offers a strategic framework integrating material and spiritual dimensions as an innovative approach to inclusive education policies.